2016
DOI: 10.1074/jbc.m116.729236
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mesenchymal Transition Induces Aberrant Glycosylation through Hexosamine Biosynthetic Pathway Activation

Abstract: Deregulated cellular metabolism is a hallmark of tumors. Cancer cells increase glucose and glutamine flux to provide energy needs and macromolecular synthesis demands. Several studies have been focused on the importance of glycolysis and pentose phosphate pathway. However, a neglected but very important branch of glucose metabolism is the hexosamine biosynthesis pathway (HBP). The HBP is a branch of the glucose metabolic pathway that consumes ϳ2-5% of the total glucose, generating UDP-GlcNAc as the end product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 62 publications
4
88
2
Order By: Relevance
“…Another recent paper showed that Snail regulates glycolytic activity by suppressing transcription of PFKP, which directs the glucose flux toward the PPP (Kim et al, 2017). Although the authors have noticed that this metabolic regulation of PFKP occurs independently of EMT program, we showed a decreased level of PFKP enzyme during EMT (Lucena et al, 2016). Although the authors have noticed that this metabolic regulation of PFKP occurs independently of EMT program, we showed a decreased level of PFKP enzyme during EMT (Lucena et al, 2016).…”
Section: O-glcnac In Cancer and Emtcontrasting
confidence: 61%
See 1 more Smart Citation
“…Another recent paper showed that Snail regulates glycolytic activity by suppressing transcription of PFKP, which directs the glucose flux toward the PPP (Kim et al, 2017). Although the authors have noticed that this metabolic regulation of PFKP occurs independently of EMT program, we showed a decreased level of PFKP enzyme during EMT (Lucena et al, 2016). Although the authors have noticed that this metabolic regulation of PFKP occurs independently of EMT program, we showed a decreased level of PFKP enzyme during EMT (Lucena et al, 2016).…”
Section: O-glcnac In Cancer and Emtcontrasting
confidence: 61%
“…In general, cancer cells during EMT enhance glycolysis and glucose uptake. 1) (Lucena et al, 2016). Kondaveeti and colleagues showed an increase in glycolysis and a decrease in gluconeogenesis during EMT using two different breast cancer cell lines (Kondaveeti et al, 2015).…”
Section: Emt: General Aspects and Glucose Metabolismmentioning
confidence: 99%
“…In addition, the actin binding protein cofilin is O-GlcNAcylated, which is required for its proper localization to invadopodia of breast cancer cells and contributes to breast cancer cell invasion 68 . Recent studies have shown that EMT in lung cancer cells increases flux through the HBP and increases O-GlcnAcylation 69 . These data indicate possible crosstalk between O-GlcNAcylation and EMT programs that may contribute to fine-tuning cancer cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…During EMT, epithelial cells acquire certain characteristics of the stromal cells around them, as seen by the loss of epithelial polarity and the acquisition of stromal features, including a stromal-like appearance, and vimentin, snail, and osteopontin expression [10, 11]. Epithelial cells often change from a cobblestone-shape to a spindle-shape, the level of E-cadherin decreases, and those of vimentin, α-SMA, and fibronectin increase; after EMT, epithelial cells show functional similarity to fibroblasts.…”
Section: Introductionmentioning
confidence: 99%